Impact of socio-economic status and race on emergency hospital admission outcomes: Analysis from hospital admissions between 2001 and 2012. (August 2022) - Davidson, Thomas; Mirza, Farhaan; Baig, Mirza M
Abstract: Socio-economic and racial/ethnic disparities in healthcare quality have been the point of huge discussion and debate. There is currently a public debate over healthcare legislation in the United States to eliminate the disparities in healthcare. We reviewed the literature and critically examined standard socio-economic and racial/ethnic measurement approaches. As a result of the literature review, we identified and discussed the limitations in existing quality assessment for identifying and addressing these disparities. The aim of this research was to investigate the difference between health outcomes based on patients' ability to pay and ethnic status during a single emergency admission . We conducted a multifactorial analysis using the 11-year admissions data from a single hospital to test the bias in short-term health outcomes for length of stay and death rate, based on 'payment type' and 'race', for emergency hospital admissions. Inconclusive findings for racial bias in outcomes may be influenced by different insurance and demographic profiles by race. As a result, we found that the Self-Pay (no insurance) category has the shortest statistically significant length of stay. While the differences between Medicare, Private and Government are not significant, Self-Pay was significantly shorter. That 'Whites' have more Medicare (older) patients than 'Blacks' might possibly lead to a longer length of stay and higher death rate for the group.